Optimization of Imam Santri Scheduling at the Griya Tilawah Islamic Boarding School in the Areas Around Malang Using Genetic Algorithms - Nur Lailatul Aqromi; Zainal Abidin; Siti Nurul Afiyah (Procedia of Engineering and Life Science, 2021)
Every holy month of Ramadhan, the students will be placed in certain mosques around Malang to become imams. While every year there are always additional students, and the ability of each student is different. Therefore, every year the priest must re-schedule. One method that can be used to solve these problems is to use genetic algorithms. After forming the initial population, the individuals will be selected whether they are in accordance with what is expected or not. From the results of the selection will form a new population that is better. So it is expected that the resulting schedule is optimal.